Large and Complex Financial Institutions : Challenges and Policy Responses; Lessons from Sweden - Johnston, R. (IMF Policy Discussion Papers; Policy Discussion Paper, 2003)
This paper examines the regulatory and supervisory implications stemming from the dominance of large and complex financial institutions, drawing on the recent Financial Sector Assessment Program (FSAP) mission work on Sweden. The analysis highlights the importance of consolidated supervision, of a greater emphasis on effective management and corporate governance structures, and of measures strengthening the disciplinary role of the private sector. It calls for developing credible liquidity and crisis management arrangements through appropriate attention to the cross-product and cross-border nature of large and complex financial institution (LCFI) operations. Strengthened supervisory and regulatory responses will enable financial markets to better assess the nature and sources of residual risks they have to face and, on this basis, to develop more effective risk-mitigating measures.